Effects of chemical, biological, and integrated management of waterhyacinth (Pontederia crassipes) on small fish - Sara Schutt; Ashley B. C. Goode; Melissa C. Smith; Lyn A. Gettys; J. Matthew Hoch (Wetlands Ecology and Management, 2025)

Early signals of fragmentation of flat-tailed horned lizards in the Yuma Desert - Natalie Payne; Anthony J. Pawlicki; Eldridge Wisely; Karla L. Vargas; John A. Erwin; Melanie Culver; Matt Goode (Conservation Genetics, 2025)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Bridging the spawner-recruit disconnect II: Revealing basin-scale correlations between zooplankton and lobster settlement dynamics in the Gulf of Maine - Burton Shank; Joshua T. Carloni; Paul Geoghegan; David M. Fields; Andrew G. Goode; Harvey J. Walsh; Richard A. Wahle (Fisheries Research, 2024)

Natural Canopy Disturbance Patterns and Ecological Silviculture in the Alabama Fall Line Hills - Aurora C Baker; David L Phillips; J Davis Goode; Justin L Hart (Forest Science, 2024)
As a natural disturbance-based approach to silviculture is increasingly embraced by forest managers, quantitative reference conditions of natural disturbance patterns are paramount. We used LiDAR data to quantify resultant structural patterns from an EF3 tornado on the Oakmulgee Ranger District of Talladega National Forest in the Alabama Fall Line Hills, USA. We found the zone of catastrophic disturbance totaled 123 ha, had a mean width of 360 m, and residual trees were randomly distributed. This zone was buffered by an edge zone of intermediate-severity disturbance where trees were removed individually and in groups. The edge zone averaged 220 m in width. In total, the study area included seventy-nine stands and the percentage of stand area damaged ranged from < 1% to 94%. We suggest that clearcut, seed tree, and shelterwood with reserves regeneration methods may be appropriate analogs to natural canopy disturbance in the Fall Line Hills region. These catastrophic disturbance entries should be buffered from undisturbed neighborhoods by a system that retains mature forest structures and would constitute a zone of intermediate-severity disturbance. Our approach may be used as a template to expand our understanding of natural canopy disturbance patterns in other regions and forest types. Study Implications: In regions where tornadoes are a natural component of the disturbance regime, including much of the southeastern United States, we suggest that clearcut, seed tree, or shelterwood with reserves regeneration methods may be used to approximate the zone of catastrophic disturbance that corresponds to the tornado track. We observed that reserve tree spatial patterns were random, but residual trees could be selected based on desired species or protection of important biophysical features such as seeps. Surrounding the catastrophic disturbance zone was an edge zone of intermediate-severity disturbance where trees were removed individually and in variably sized groups. We suggest that the structural patterns documented in this edge zone may be created through variable retention harvesting.

Implications for the conservation of deep-water corals in the face of multiple stressors: A case study from the New Zealand region - Fabrice Stephenson; Ashley A. Rowden; Owen F. Anderson; Joanne I. Ellis; Shane W. Geange; Tom Brough; Erik Behrens; Judi E. Hewitt; Malcolm R. Clark; Dianne M. Tracey; Savannah L. Goode; Grady L. Petersen; et al. (Journal of Environmental Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Spatial Patterns of Canopy Disturbance and Shortleaf Pine in a Mixedwood Forest - J Davis Goode; Justin L Hart; Daniel C Dey; Scott J Torreano; Stacy L Clark (Forest Science, 2021)
The spatial structure of forest ecosystems is dominated by the horizontal and vertical distribution of trees and their attributes across space. Canopy disturbance is a primary regulator of forest spatial structure. Although the importance of tree spatial pattern is widely acknowledged as it affects important ecosystem processes such as regeneration and recruitment into the overstory, quantitative reference spatial conditions to inform silvicultural systems are lacking. This is especially true for mixedwood forests, defined as those that contain hardwoods and softwoods in the canopy. We used data from a preexisting network of plots in a complex-stage mixedwood stand to investigate the influence of canopy disturbance on stand and neighborhood-scale spatial patterns. We reconstructed canopy disturbance history and linked detected stand-wide and gap-scale disturbance events to establishment and spatial patterns of shortleaf pine. The majority of shortleaf pine establishment coincided with stand-wide or gap-scale disturbance. Shortleaf pine was clustered at the stand scale but was randomly distributed at the neighborhood scale (i.e. five tree clusters), which was a legacy of the historical disturbance regime. These results may be used to improve natural disturbance-based silvicultural systems to restore and maintain mixedwood forests for enhanced resilience and provisioning of ecosystem goods and services.

Phospho-substrate profiling of Epac-dependent protein kinase C activity - Diana J. Goode; Derek C. Molliver (Molecular and Cellular Biochemistry, 2019)

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Map visualization of groundwater withdrawals at the sub-basin scale - Daniel J. Goode (Hydrogeology Journal, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Organochlorine Pesticides in Squamate Reptiles from Southern Arizona, USA - Scott M. Weir; Marianne Dobrovolny; Chelsea Torres; Cassie Torres; Matt Goode; Thomas R. Rainwater; Christopher J. Salice; Todd A. Anderson (Bulletin of Environmental Contamination and Toxicology, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Bathymetry Retrieval from Hyperspectral Imagery in the Very Shallow Water Limit: A Case Study from the 2007 Virginia Coast Reserve (VCR'07) Multi-Sensor Campaign - Charles M. Bachmann; Marcos J. Montes; Robert A. Fusina; Christopher Parrish; Jon Sellars; Alan Weidemann; Wesley Goode; C. Reid Nichols; Patrick Woodward; Kevin McIlhany; Victoria Hill; Richard Zimmerman; et al. (Marine Geodesy, 2010)

The effect of a lipid suspension on amitriptyline disposition - N. A. Minton; A. G. Goode; J. A. Henry (Archives of Toxicology, 1987)